Criteria for evaluating scientific publication in refereed scientific journals - hafidha Khelifi (Social Empowerment Journal, 2021)
The scientific output reached by researchers in various sciences needs to be generalized and disseminated, as the importance of scientific publishing as a provider of knowledge to all researchers appears, and one of its types is publishing in refereed scientific journals. Which came as a mechanism to deter unethical publications, and as a goal to protect copyright and intellectual rights of researchers? Thus, researchers and academic and research bodies from universities and research centers have been interested in reliable and controlled scientific publishing, as a large number of researchers seek to publish their research in refereed scientific journals. Hence, this article came as a goal to answer the following question: What are the criteria for evaluating scientific publication in refereed scientific journals?It was concluded that, although publishing in these journals and the classification of them is one of the conditions for obtaining a scientific certificate or academic promotion, there are researchers who reject their research for not following the standards adopted by scientific journals in scientific publishing, where the work of researchers sent to These journals are judged by the reviewers, who accept only articles that comply with the scientific publishing rules adopted by the journal, starting with the researcher’s consideration of the period specified by the journal to send the articles and the affiliation of the research subject to the journal’s specialization and interests, passing through criteria related to the form and content of the research to the validity of the research for publication. .